As bombas de prótons do tonoplasto de hipocótilos de Vigna unguiculata (L.) Walp e sua participação no estresse salino - Otoch, Maria de Lourdes Oliveira (1999)
The transmembrane proton pumps, H+-ATPases and H+-PPase, work as mechanisms of primary transport in plant cells and both enzymes generate an electrochemical proton potential through the vacuolar membrane functioning by the H+/substrate antiporter transport mechanism. In the present work, initially the distribution of the proton pumps, H+-ATPases and H+-PPase, were determined in different endomembranes of tonoplast from hypocotyl of Vigna unguiculata (L.) Walp cv. Vita 5 with a 25 % sucrose gradient. The functioning of H+-ATPases and H+-PPase has been evaluated through the hydrolytic and proton transport activities. The effects of the temperature, pH, ions, and inhibitors on W-ATPases and W-PPase, as well the kinetic parameters (Km and Vmax) have been studied. Indicative parameters of saline stress have been determined in two cultivars of Vigna unguiculata (L.) Walp, with different degrees oftolerance to salinity (Vita 3, more tolerant and Vita 5, less tolerant). It has been verified that 100 mM NaCl induced ca. 50 % decrease of the growth of the plant aerial part of the less tolerant cultivar. The activities of the mitochondrial ATPase, V-ATPase and H+-PPase from seedling of Vita 5 cultivar were studied. It has been verified that the activities of mitochondrial ATPase and V-ATPase decrease along the time in hypocotyls and in 7-day-old epicotyls. PPase activity of tonoplasts also decreases from 3 to 7 day old hypocotyl but increases in 7-day-old epicoty1. The decline of V-ATPase activity from hypocotyls and epicotyls , along the time, might be correlated to the decrease of mitochondrial ATPase activity. As a growth developing tissue, the 7-day-old epicotyl utilizes PPase that is the key enzyme in the processes of the plant growth and development. A companson between hydrolytic and proton transport activities of V-ATPases and H+-PPase of tonoplast in salt stress conditions was done and it has been verified that, after 7 days of salt treatment the activities of V-ATPase increased while PPase activities decreased. The westem blotting analysis of the A and B subunits of V-ATPase revealed that, the protein content of the 2 subunits increased or decreased according to their activities, while the protein content of PPase presented a different pattem as compared to its activity. The present results suggest that, the saline stress induce a different regulation of the two vacuolar proton pumps during plant tissue elongation as compared to the control. V-ATPase and H+-PPase are independently regulated in saline stress conditions.